2021
DOI: 10.3390/met11060987
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylic Acid to Improve Flotation Tailings Management: Understanding the Chemical Interactions through Molecular Dynamics

Abstract: Molecular dynamic simulations of polyacrylic acid polyelectrolyte (PAA) analyzed its interaction with the main minerals that make up characteristic tailings of the mining industry, in this case, quartz, kaolinite, and montmorillonite. The simulations were carried out with the package Gromacs 2020.3. The interaction potentials used were General AMBER Force Field (GAFF) for PAA and CLAYFF-MOH for mineral surfaces. The SPC/E model described water molecules and Lennard-Jones 12-6 parameters adjusted for SPC/E mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The methodology to build molecules follows our previous work [13,36]. To accomplish this, the polymer NaPA was meticulously designed, comprising 48 acrylate monomers (-CH 2 -CHCOO − -), which underwent complete dissociation due to the monomers' pKa of 4.5.…”
Section: Molecules and Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology to build molecules follows our previous work [13,36]. To accomplish this, the polymer NaPA was meticulously designed, comprising 48 acrylate monomers (-CH 2 -CHCOO − -), which underwent complete dissociation due to the monomers' pKa of 4.5.…”
Section: Molecules and Surfacesmentioning
confidence: 99%
“…In the context of mineral processing, it finds common usage in the mining industry as a dispersant additive for enhancing the flotation stage's efficiency and improving tailings fluidity. NaPA is watersoluble; its salts are neutralized at molecular masses up to 100,000 g/mol [11][12][13]. This constitutes a fundamental consideration, given its significant impact on rheological properties and dispersion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…PAA was selectively adsorbed on calcite, selectively depressed, and improved fluorite recovery with sodium oleate at pH 7. Quezada et al [24] reported that applying PAA could improve the sedimentation and storage of quartz, montmorillonite, and kaolinite flotation tailings. Through molecular dynamics simulation, PAA was reported to adsorb on quartz and clay mineral surfaces, ultimately preventing agglomeration of the tailings and allowing easy dewatering.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that, with the increase of the average molecular weight of sodium petroleum sulfonate, the flotation recovery of fluorite gradually decreased. Quezada et al [16] used Gromacs software to study the adsorption behavior of polyacrylic acid polyelectrolyte (PAA) on the surface of quartz, kaolinite, and montmorillonite. Molecular simulation can not only be used to reveal the interaction between collectors and kaolinite [17][18][19], quartz [20][21][22], fluorite [23], and other crystal minerals [24,25] but also can simulate the interaction between coal and collectors [26].…”
Section: Introductionmentioning
confidence: 99%